PELATIHAN TEKNIK PEMBUATAN JUMPUTAN PADA MEDIA TOTEBAG UNTUK MENINGKATKAN KETERAMPILAN DAN MENUMBUHKAN JIWA WIRAUSAHA ANAK-ANAK PANTI ASUHAN BAKTI MULIA PALEMBANG - Ade, Sri Ade Kayanti; Naufal Najib; Puja Rahmanu Gusmer; Wulan Triyuni Damayanti; Mukti Rahayu; Putri Amelia Muharram Zu; Rana Karimah; Alfiandra; Ria Amanda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Jumputan batik is one type of batik that uses binding and dyeing techniques according to the desired color. This training activity on jumputan making techniques on totebag media uses training and mentoring methods directly to the parties involved. The techniques used include socialization, discussion, and hands-on practice. The making of Jumputan batik totebags is expected to be a place for children to be able to express themselves, develop creativity, and broaden their horizons about art and hand skills. they can express their imagination freely from the thoughts of orphanage children. The training on jumputan technique on totebag media produces unique works that are the result of a personal touch. Before the training, their understanding was only 18%. However, after attending the training, their understanding increased to 94% through the results of the questionnaire survey that has been conducted. With the training practice of making jumputan techniques on totebag media, it provides a fun new experience for children of Bakti Mulia Orphanage Palembang, and can foster an entrepreneurial spirit that provides business opportunities for children of Bakti Mulia Orphanage Palembang.